The aesthetic of Arabic calligraphy in Saudi plastic painting - Alsudairy, Maha Mohammed (Journal of Humanities & Social Sciences, 2023)
The research aims to reveal the aesthetic values of Arabic calligraphy in Saudi plastic photography; and also to reveal the contemporary styles, techniques and methods of performance that characterized Saudi plastic artists to form their unique identity inspired by Arabic calligraphy and addressed by each artist in his plastic production. To achieve this goal, some of the works of contemporary Saudi artists have been analyzed to reveal the aesthetic values of Arabic calligraphy and the different approaches addressed by each of them, so that through them the field of plastic photography can be enriched with different vocabulary as well as enrich the approaches of plastic photography by finding new entrances, as well as confirming the national identity of some of the Kingdom’s artists by shedding light on their works. The research follows the descriptive and analytical approach through the theoretical framework, which deals with the study of a number of points that illustrate the importance of Arabic calligraphy, and the creativity of the Muslim artist in Arabic calligraphy, and the study deals with the explanation and analysis of a selection of works of contemporary Saudi artists who relied in their compositions on Arabic calligraphy. As a result, artists were able to find an expressive approach in an innovative way in formulating that subject in a new and innovative formulation based on his experiences and artistic expertise, so his expressive works came strong and honest characterized by their artistic composition and creative aesthetic, and the artist controlled his physical media in different ways and techniques that he mastered in using within his artworks to suit his subject and expression .The researcher recommends paying attention to finding new approaches and starting points that enrich the field of contemporary Saudi plastic photography, and to emphasize the national identity of the works of the Kingdom’s artists in which national, heritage and religious elements and symbols are addressed.